Fundamentals of gas reservoir engineering - Hagoort, Jacques; ScienceDirect eBooks (Amsterdam ; New York : Elsevier ; New York, NY, U.S.A. : Distributors for the U.S. and Canada, Elsevier Science Pub. Co., 1988)
Gas reservoir engineering is the branch of reservoir engineering that deals exclusively with reservoirs of non-associated gas. The prime purpose of reservoir engineering is the formulation of development and production plans that will result in maximum recovery for a given set of economic, environmental and technical constraints. This is not a one-time activity but needs continual updating throughout the production life of a reservoir. The objective of this book is to bring together the fundamentals of gas reservoir engineering in a coherent and systematic manner. It is intended both for students who are new to the subject and practitioners, who may use this book as a reference and refresher. Each chapter can be read independently of the others and includes several, completely worked exercises. These exercises are an integral part of the book; they not only illustrate the theory but also show how to apply the theory to practical problems. Chapters 2, 3 and 4 are concerned with the basic physical properties of reservoirs and natural gas fluids, insofar as of relevance to gas reservoir engineering. Chapter 5 deals with the volumetric estimation of hydrocarbon fluids in-place and the recoverable hydrocarbon reserves of gas reservoirs. Chapter 6 presents the material balance method, a classic method for the analysis of reservoir performance based on the Law of Conservation of Mass. Chapters 7-10 discuss various aspects of the flow of natural gas in the reservoir and the wellbore: single phase flow in porous and permeable media; gaswell testing methods based on single-phase flow principles; the mechanics of gas flow in the wellbore; the problem of water coning, the production of water along with the gas in gas reservoirs with underlaying bottom water. Chapter 11 discusses natural depletion, the common development option for dry and wet gas reservoirs. The development of gas-condensate reservoirs by gas injection is treated in Chapter 12. Appendix A lists the commonly used units in gas reservoir engineering, along with their conversion factors. Appendix B includes some special physical and mathematical constants that are of particular interest in gas reservoir engineering. Finally, Appendix C contains the physical properties of some common natural-gas components.
Includes bibliographical references and indexes.
Print version record.
Elsevier
Keywords: Gas reservoirs; TECHNOLOGY & ENGINEERING -- Mining; Gas reservoirs; Natural gas deposits -- Reservoirs -- Exploitation -- Engineering aspects; Electronic books